Factors predicting lower limb alignment after Oxford medial unicompartmental knee arthroplasty - Han-Ting Shih; Kun-Hui Chen; Cheng-Hung Lee; Kao-Chang Tu; Shun-Ping Wang (Scientific Reports, 2024)
Abstract This study aimed to identify the factors affecting hip−knee−ankle (HKA) angle following Oxford medial unicompartmental knee arthroplasty (MUKA). A retrospective analysis of 200 patients who underwent Oxford MUKA from June 2018 to October 2020 was conducted. Univariate and multivariate analyses were performed to investigate the impact of surgical and radiographic characteristics on the postoperative HKA angle. The mean HKA angle was 9.5 ± 4.3° before surgery and 3.6 ± 3.7° after surgery (p < 0.001). The postoperative HKA angle significantly correlated with the preoperative HKA angle, bearing size, tibial component alignment angle, and BMI (r = 0.71, p < 0.001; r =  − 0.24, p = 0.001; r = 0.21, p = 0.004; r =  − 0.18, p = 0.011). Multiple linear regression analysis revealed that the preoperative HKA angle (β = 0.68, p < 0.001), bearing size (β =  − 0.31, p < 0.001), tibial component alignment angle (β = 0.14, p = 0.003), and BMI (β =  − 0.09, p = 0.047) significantly affected the postoperative HKA angle. In conclusion, larger preoperative varus deformity, smaller bearing size, greater varus alignment of the tibial component, and lower BMI lead to greater postoperative varus alignment of the lower limb in Oxford MUKA. With this concept, surgeons can more accurately predict postoperative lower limb alignment and avoid malalignment in Oxford MUKA.